FEATURES OF PERCEPTION OF LOADING ELEMENTS OF THE RAILWAY TRACK AT HIGH SPEEDS OF THE MOVEMENT - Kurhan, D. M. (Science and Transport Progress, 2015)
Purpose. Increase the train speeds movements requires not only the appropriate technical solutions, but also methodological-calculated. Most of the models and methodologies used for solving problems of stress-strain state of the railroad tracks, are based on assumptions and hypotheses adequate only for certain speeds. In the framework of this work will be discussed theoretical background of the changing nature of perceptual load elements of the railway track at high speeds and investigated the numeric parameters of the processes by means of mathematical modeling. As a practical purposes is expected to provide the levels of train speed, the boundaries of which can reasonably exclude the possibility of occurrence of the considered effects. Methodology. To achieve these objectives was used principal new model of railway track based on wave propagation theory stresses in the elastic system to study the impact of the movable load, take into account that the deflection in a particular section of the road starts even while the wheels at some distance, and moving the wheels farther from the selected section of the wave front elastic strain continues to spread. According to the results of simulations explores the changing shape of the wave front voltages in time for the foundation under the rail. If the train speeds substantially less than the velocity propagation of elastic waves, the wheel remains in the area implemented deformations. Findings. Alternative calculations for various parameters of the railway track (especially for different soil conditions) determined the levels of train speed, the boundaries of which can reasonably exclude the possibility of occurrence of the considered effects. Originality. The proposed theoretical study and implementation in the form of mathematical models for processes that occur in the perception of load elements of the railway track at high speeds. Practical value. According to simulation results obtained levels of speeds, which define the appearance of the considered dynamic effects in the base under the rail, can be used to justify path construction or establishment of appropriate values of allowable velocities for the implementation of traffic at high speeds.